Effects of Seawater Temperature and Salinity on Physiological Performances of Swimming Shelled Pteropod Creseis acicula During a Bloom Period - Han, Tingting; Qi, Zhanhui; Shi, Rongjun; Liu, Qingxia; Dai, Ming; Huang, Honghui (Frontiers in Marine Science, 2022)
Creseis acicula is a swimming shelled pteropod species, widely distributed in the world’s oceans. In 2020, an unprecedented bloom of C. acicula was observed in Daya Bay, and lasted from June to July. To date, there is very limited information on the physiological characteristics of this species, which is essential to understand bloom dynamics. In the present study, the physiological performances of C. acicula in response to temperature (17‒35 ºC) and salinity (18‒38 ppt) were investigated. The oxygen consumption (OCR) and calcification rates (CR) of C. acicula peaked at 32 and 26 ºC, respectively, while ammonia excretion rate (AER) significantly increased with increasing temperature. The thermal coefficient Q10 (respiration) of C. acicula dropped to a minimum value between 32 and 35 ºC, suggesting that they were in a stressful status. The O:N ratio ranged from 3.24 to 5.13, indicating that protein was the major catabolism substrate. Temperature exerted a stronger effect on the OCR and AER of C. acicula. Salinity has a more influence on CR. The preferable temperature for C. acicula ranges from 29 to 32 ºC, and the preferable salinity ranges from 28 to 33 ppt. Based on a comprehensive consideration, we presumed that the warmer seawater temperature around the thermal discharge area of Daya Bay nuclear power plant is a possible cause for the bloom of C. acicula.